From ECG to Ablation: A Modern Review of Wolff-Parkinson-White Syndrome - Krupa, Agata; Potrykus, Maria; Klasicki, Przemysław; Maciej Mozer; Wiktor Możarowski; Anna Krawczyk; Michał Pałuchowski; Jan Mateńko; Julia Kiełbratowska; Wiktoria Pietruszka (Quality in Sport, 2025)
Wolff-Parkinson-White (WPW) syndrome is a clinical manifestation of pre-excitation syndrome, characterized by the congenital presence of an additional conduction pathway in the form of a muscle fibre - Kent’s bundle between the atria and ventricles, resulting in paroxysmal supraventricular tachycardia and increasing the risk of sudden cardiac death when atrial fibrillation occurs. The aim of this study is to show a structured knowledge of the pathophysiology and epidemiology, clinical manifestations, diagnosis, risk assessment and management of Wolff-Parkinson-White syndrome based on a review of the literature, Pubmed and Google Scholar databases. Based on current data, the prevalence of electrographic features of pre-excitation is estimated at 0.15-0.25% in the general population. The presence of an additional conduction pathway between the ventricles, predominantly conducting impulses like healthy His and Purkinje fibres, results in a characteristic ECG pattern, allowing the diagnosis of pre-excitation syndrome. Each excitation from sinoatrial node is conducted not only by the physiological pathway, but also by an accessory pathway, the clinical consequences of which will be the occurrence of supraventricular tachycardias such as an orthodromic and antidromic atrioventricular reentrant tachycardia (AVRT), atrial fibrillation or even the ventricular fibrillation, which can be the first symptom of the syndrome. The diagnosis is aided by electrophysiology studies (EPS) to confirm the presence of an accessory pathway, with usually simultaneous invasive treatment - percutaneous ablation, which is also a causal therapy with an efficacy of approximately 92%. Pharmacological treatment of patients with WPW is based on group IA and IC antiarrhythmic drugs, but these act only for symptoms, they are ineffective in eliminating the underlying cause of disease.